Non‐destructive DNA extractions from fly larvae (Diptera: Muscidae) enable molecular identification of species and enhance morphological features. Issue 4 (4th September 2019) - Martoni, Francesco; Valenzuela, Isabel; Blacket, Mark J
Abstract: Insects preserved as reference specimens are important in a wide range of fields, including health, pest management and forensics. The aim of the present study was to test a non‐destructive DNA extraction method on samples of soft‐bodied insects, fly larvae, which are otherwise hard to identify morphologically. This not only provides DNA enabling molecular identification but also retains morphological reference specimens for samples belonging to collections and museums that cannot be destroyed. In this work, fly larvae identified as belonging to the family Muscidae were non‐destructively processed. DNA barcoding molecular identification allowed most of these specimens to be assigned to species. Furthermore, the visibility of seven important larval morphological characters – anterior and posterior spiracles, mouth hooks, cephalopharyngeal skeleton, locomotory welts, segmentation and colour – was assessed pre‐ and post‐DNA extraction. It was found that the morphology generally did not deteriorate post‐DNA extraction but actually improved through increased visibility of internal features. Therefore, this non‐destructive DNA extraction method not only allowed COI barcode sequences to be obtained, but also enabled a better morphological identification of the fly larvae retaining physical reference voucher specimens and avoiding the need for dissections.